A comparison study of ride comfort indices between Sperling's method and EN 12299. Issue 4 (2nd October 2019) - Jiang, Yanran; Chen, Bernard K.; Thompson, Cameron
ABSTRACT: Ride comfort refers to human tolerance to vibration exposure over time. Presently, ISO 2631, EN 12, 299 and Sperling's method are the most common evaluation methods for assessing passenger comfort on trains. It is difficult to establish a universal set of requirements because passengers' perception of comfort may be affected by various factors such as vibration, noise, track condition, etc. In this paper, existing standards and methods for evaluating ride comfort are assessed. A case study of V/Line passenger train in Australia in which the dynamic response is measured and used to evaluate the Continuous Comfort index, Mean Comfort index, and Sperling index. Based on the previous findings and the experimental results, similarities and benefits between these ride comfort methods are analysed and discussed. A new compound Sperling's index is proposed and the correlations of various ride comfort indices are established.